Evaluation of Urban Drainage Capacity in Relation to Surface Flooding in Lowokwaru District, Malang City - Asmaranto, Runi; Harisuseno, Donny; Palla, Anna (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Urban surface flooding has become a recurrent problem in rapidly urbanizing cities in Indonesia, including Malang City. The Lowokwaru District, as an educational and residential hub, frequently experiences inundation during moderate to high rainfall events, indicating potential inadequacy in its urban drainage system. This study aims to evaluate urban drainage capacity in relation to surface flooding in Lowokwaru District through a comprehensive synthesis of empirical studies, modeling-based evaluations, and spatial analyses conducted over the past decade. A qualitative-descriptive and comparative approach was employed by reviewing and integrating results from peer-reviewed journal articles that applied hydrological–hydraulic analysis, EPA SWMM modeling, GIS-based evaluation, and eco-drainage concepts. The results indicate that a significant proportion of drainage channels in Lowokwaru are unable to convey design flood discharges for 5- to 10-year return periods due to insufficient channel dimensions, sedimentation, debris accumulation, and rapid land-use change. Several studies demonstrate that structural improvements alone are insufficient; instead, integrated solutions such as Low Impact Development (LID), infiltration wells, detention ponds, and eco-drainage strategies can reduce surface runoff and flooding by 40–70%. This study concludes that urban drainage management in Lowokwaru requires a systemic and sustainable approach that integrates hydraulic capacity enhancement with land-use control and nature-based solutions. The findings provide a consolidated scientific basis for urban flood mitigation planning in Malang City and similar rapidly urbanizing areas.